ANALISIS SUDU DAN GIGI PENERUS TURBIN UAP PENGGILING TEBU DI. PT. PG. RAJAWALI II JATITUJUH KABUPATEN MAJALENGKA - Sutrisno, Azzy; M. Yunus, Riza (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Steam turbine is a prime mover that converts steam potential energy into kinetic energy and then is converted into mechanical energy in the form of turbine shaft rotation. The turbine shaft, directly or with the aid of a reduction gear, is connected to the mechanism to be moved. Maintenance is a function that is as important as production in a company or factory. This is because the equipment or facilities that we use require maintenance or maintenance so that the equipment or facilities can be used continuously so that production activities can run smoothly. From the results of the preparation of the Job Training Report about the working process of sugar cane steam turbine turbines in PT. PG. RAJAWALI II Jatitujuh majalengka, this can be concluded as follows: There is a finding how to overcome the problematic steam turbine blades is to maintain the quality of the boiler steam so it does not go up and down, because if the quality of the steam in the boiler goes up and down will cause corrosion blades, if the longer will be broken on the blades, and if broken blade will cause a lack of performance on the turbine. The rotation speed corresponding to the turbine and the successor gear is 6500 rpm at the turbine rotation of 5 rpm at the final successor gear rotation.